Effects of steel fibres on hammer drilling in concrete for the installation of post-installed anchors. (15th July 2022) - Spyridis, Panagiotis; Walter, Lars; Biermann, Dirk; Dreier, Julia
Abstract: Dispersed short steel fibres can be used as an addition to the concrete matrix as reinforcement to improve the material's macroscopic characteristics such as tensile strength, ductility and toughness. On the other hand, fibres may lead to negative effects in terms of constructability. For post-installed anchors, the tensile performance of the concrete plays a decisive role in certain failure mechanisms, and some fundamental investigations have already been performed in this respect. Studies on the influence of steel fibres on drilling and the respective installation have not been presented yet, although the installation quality is very significant for the fastener's load-bearing performance. This study aims to provide insight into the bearing interface characteristics of post-installed anchors and the boreholes in steel fibre-reinforced concrete generated by hammer drilling. This interface is of high importance for the performance of anchorages in special concrete composites such as steel fibre-reinforced concrete. To investigate this aspect, the research investigation is based on a combination of sophisticated but practical experimental methods ranging from drilling tool performance monitoring, qualitative and quantitative wear analysis of the borehole, optical and scanning electron microscopy of the inner borehole surface. The studies yield original findings on the interaction between drilling equipment and steel fibre-reinforced concrete in the context of the installation of post-installed anchors. Highlights: First worldwide study on hammer drilling in steel fibre concrete. Steel fibres increase the roughness of boreholes in concrete. Steel fibres in concrete may influence construction logistics and workmanship. Simultaneous analysis of drill-bit wear, drill machine power, borehole roughness.